Addressing international students on Australian and Chinese university webpages: A comparative study. (August 2020) - Zhang, Zuocheng; Tan, S.; Wignell, P.; O'Halloran, K.
Highlights: Australian and Chinese university theme pages differed in salient ways. International students were agentive individuals to explore at Australian universities. International students were guided through study abroad at Chinese universities. The verbals and visuals are indexical of different cultural practices in communication. The differences reflect varied responses to neoliberal thinking in higher education. Abstract: This article investigates the discursive construction of international students on Australian and Chinese university webpages that are directed at international students. The international student theme webpages of three Australian and three Chinese universities were examined in relation to how verbal and visual semiotic resources were co-deployed on the webpages to address international students in the climate of neoliberal thinking in higher education. The tools used for analysis and interpretation were informed by socio-semiotic approaches to multimodal discourse analysis, international education discourses and communication accommodation theories. It was found that the Australian and Chinese university webpages differed in several salient ways to the effect that international students were portrayed as agentive and informed individuals to explore a study abroad experience at the Australian universities versus being explicitly guided through their study abroad at the Chinese universities. These results were compared and interpreted as reflecting each country's conception of transnational education. The article concludes with a summary of the impacts of cultural and intercultural factors and neoliberal thinking in higher education on multimodal representations of international students on university webpages and directions for further research.